VERBAL VIOLENCE PERFORMED BY SUPPORTERS’ GROUP OF GUBERNATORIAL CANDIDATES IN THE POLITICAL DISCOURSE OF JAKARTA ELECTION - Tria Putri Mustika; Agustina Agustina; Syahrul Ramadhan (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2019)
This study aimed to describe the verbal violence performed by supporters’ group of gubernatorial candidates in the discourse of Jakarta election 2017 in their community accounts on social media and its implications for language politeness. This research was a qualitative research with descriptive method. Analyzing data was done by content analysis method as a means to reveal, understand, and capture messages in data, and make conclusions obtained through identification and interpretation of data. The results of this study reveal that the delivery of comments by the supporters’ group in the discourse of Jakarta Gubernatorial Election 2017 was dominated by the use of sarcasm (figure of speech), combined with expressive speech acts, and bald on record strategy without further ado. The total violation of the use of politeness principle shows that verbal violence dominates the expression of comments and ‘high-potential’ comments that threaten the recipients’ face. Therefore, based on this research data, the politeness level of these selected groups is in the category of ‘impolite’.Keywords: verbal violence, politeness, speech acts, political discourseKEKERASAN VERBAL OLEH KOMUNITAS PENDUKUNG PASLON DALAM WACANA POLITIK PILKADA DKI JAKARTAAbstrakPenelitian ini bertujuan untuk mendeskripsikan kekerasan verbal oleh pendukung paslon tentang wacana Pilkada DKI Jakarta 2017 dalam akun komunitasnya di media sosial dan implikasinya terhadap kesantunan berbahasa. Penelitian ini merupakan penelitian kualitatif dengan metode deskriptif. Penganalisisan data dilakukan dengan metode analisis isi (content analysis) untuk mengungkap, memahami, dan menangkap pesan dalam data, serta membuat simpulan yang diperoleh melalui identifikasi dan penafsiran data. Hasil penelitian ini mengungkapkan bahwapenyampaian komentar oleh pendukung paslon tentag wacana Pilkada DKI didominasi dengan penggunaan majas sarkasme, jenis tindak tutur ekspresif, dan strategi terus-terang tanpa basa-basi. Pelanggaran total terhadap penggunaan prinsip kesantunan menunjukkan bahwa kekerasan verbal mendominasi penyampaikan komentar dan pendapat ‘berpotensi tinggi’ mengancam muka lawan tutur, sehingta berdasarkan data penelitian ini kesantunan berbahasa para komunitas pendukung paslon berada pada kategori ‘tidak santun’.Kata kunci: kekerasan verbal, kesantunan, tindak tutur, wacana politik